Mask Use Scale: A Scale Development Study - Mamuk, Rojjin; Dissiz, Melike (Zamensalamati Publ Co, 2023)
Background: The correct use of face masks is one of the most effective ways to prevent the transmission of COVID-19 and other respiratory infections. Objectives: The present study aimed to develop a valid and reliable measure to assess attitudes and behaviors related to face mask use in social settings. Methods: This methodological study was conducted online between July 23, 2021, and September 24, 2021. The inclusion criteria entailed an age range of >= 18 years, literacy in Turkish, use of face masks, and willingness to participate in the study. The participants of the study included 489 cases who met the inclusion criteria. Data were collected using a sociodemographic information form and the Mask Use Scale. The data were evaluated using descriptive statistics, exploratory and confirmatory factor analysis, dependent-samples t-test, Pearson correlation analysis, and Cronbach's alpha internal consistency coefficients. Results: Based on the results, 36 items of the Mask Use Scale had positive and significant item-total correlation coefficients (P<0.001). Mean scores in the test and retest demonstrated no significant difference (P>0.05). Cronbach's alpha coefficients were .76 for the mask use subscale, .77 for the hygiene subscale, .78 for the cloth mask subscale, .77 for the requirement subscale, .80 for the mask selection subscale, and .93 for the entire scale. Conclusion: As evidenced by the obtained results, the Mask Use Scale is a valid and reliable tool and can be used to determine adults' attitudes and behavior related to the use of face masks in social settings.
Keywords: Attitude; Communicable disease control; Community health; Face masks; Respiratory tract infections